Write up! A Study of Copyright Information on Library-Published Journals - Melanie Schlosser (Journal of Librarianship and Scholarly Communication, 2016)
INTRODUCTION Libraries have a mission to educate users about copyright, and library publishing staff are often involved in that work. This article investigates a concrete point of intersection between the two areas - copyright statements on library-published journals. METHODS Journals published by members of the Library Publishing Coalition were examined for open access status, type and placement of copyright information, copyright ownership, and open licensing. RESULTS Journals in the sample were overwhelmingly (93%) open access. 80% presented copyright information of some kind, but only 30% of those included it at both the journal and the article level. Open licensing was present in 38% of the journals, and the most common ownership scenario was the author retaining copyright while granting a nonexclusive license to the journal or publisher. 9% of the sample journals included two or more conflicting rights statements. DISCUSSION 76% of the journals did not consistently provide accurate, easily-accessible rights information, and numerous problems were found with the use of open licensing, including conflicting licenses, incomplete licenses, and licenses not appearing at the article level. CONCLUSION Recommendations include presenting full copyright and licensing information at both the journal and the article level, careful use of open licenses, and publicly-available author agreements.External Data or Supplements:Schlosser, Melanie, 2016, "Data from: Write Up! A Study of Copyright Information on Library-Published Journals", http://dx.doi.org/10.7910/DVN/R36SVZ, Harvard Dataverse.